The impact of increasing saline flush volume to reduce the amount of residual air in the delivery system of aortic prostheses—a randomized controlled trial - Szentiványi, András; Borzsák, Sarolta; Vecsey-Nagy, Milán; Süvegh, András; Hüttl, Artúr; Fontanini, Daniele Mariastefano; Szeberin, Zoltán; Csobay-Novák, Csaba (Frontiers in Cardiovascular Medicine, 2024)
Background: Air embolism during thoracic endovascular aortic repair (TEVAR) is associated to an incomplete deairing of the delivery system despite the saline lavage recommended by the instructions for use (IFU). As the delivery systems are identical and residual air remains frequently in the abdominal aortic aneurysm sac, endovascular aortic repair (EVAR) can be used to examine the effectiveness of deairing maneuvers. We aimed to evaluate if a more complete deairing can be achieved with increasing the flush volume. Methods: EVAR patients were randomized according to flushing volume (Group A:1xIFU & Group B: 4xIFU). Terumo Aortic Anaconda and Treo and Cook Zenith Alpha Abdominal stent grafts were implanted randomly at equal distribution (10-10-10). Air trapped in the aneurysm sac was quantified on pre-discharge CTA. Thirty patients were enrolled and equally distributed between the two groups. There were no differences in any demographic or anatomical factors.Results: Presence of air was less frequent in Group A than in Group B (7 (47%) vs. 13 (87%), p= .02), volume of air was less in Group A compared to Group B (103.5 ± 210.4 vs. 175.5 ± 175.0 mm3, p= .04). Volume of trapped air was higher with Anaconda graft type (p= .025).Discussion: Increased flushing volume is associated with more trapped air, thus following the IFU might be associated with smaller risk of air embolization. Significant differences were identified between devices regarding the amount of trapped air.